Continuum of maternal health care and the use of postpartum family planning in Nepal - Kafle, Ramesh B.; Dulal, Komal P.; Pandey, Krishna P. (DHS Working Papers No. 133, 2017)
Continuum of maternal health care is crucial for women’s reproductive health. Initiation of family planning use during the postpartum period also is crucial for both maternal and child health. Nepal has emphasized the continuity of maternal health care as well as the use of modern contraception postpartum. In this context, the paper examines the role of the continuum of maternal care on subsequent use of postpartum family planning. For the analysis, the study uses information obtained in the 2011 Nepal Demographic and Health Survey (NDHS) from women of reproductive age who reported at least one birth in the 5 years before the survey. Results show that within 12 months following the last birth, 37% of women started using a modern family planning method. Continuity in the use of maternal health care is significantly associated with contraceptive use postpartum after controlling for other socioeconomic and demographic factors. The results imply that providing a continuum of maternal health care—antenatal, delivery, and postnatal—and ensuring that all women receive this care can increase the use of postpartum contraception. It is time to consider the importance of the continuum of maternal health care and to establish responsible institutions to implement and monitor the integrated maternal child health and family planning program during the process of state restructuring and power devolution in the new federal structure in Nepal.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The DHS Working Papers series is a prepublication series of papers reporting on research in progress that is based on Demographic and Health Surveys (DHS) data. This research is carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#AID-OAA-C-13- 00095). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.